Effect of promoters (Mn, Zn and ZrO2) on the characterization of SBA-15 supported cobalt catalyst for fischer-tropsch synthesis - Muhammad Suhaimi, Man (2012)
Fischer–Tropsch synthesis (FTS) is a part of gas-to-liquids (GTL) technology,which produces synthetic liquid hydrocarbons from natural gas.Recently the production of clean fuels and particularly of synthetic diesel by means of the FTS process has aroused renewed interest in both industrial and academic field.This process was shown to be catalyzed by certain transition metals,such as Co which present the highest activity.This research work is about the synthesis of SBA-15 and preparation of catalyst with different promoter Zr, Zn, Mn – Co based supported by SBA-15 by wet impregnation catalysts and characterizes all sampling.All materials were characterized by several physico-chemical techniques such as TGA,SEM and FTIR.The catalytic and characterization results show a great influence of mesoporous support porosity on the structure, reducibility and FTS catalytic behavior of cobalt oxide species supported over these ordered materials.After modification of SBA-15 by Co with different loading,the particles found to be attached closely with each other.The SEM picture shows a large number of SBA-15 particles attaching closely with one another.So this will make catalyst more efficient and effective during FT process. Then,using FTIR,the functional groups will be observed with certain wavelength in the samples such as cobalt oxides,Si-O-Si,Si-CH3,zinc oxide,OH band, Si-C,and others.Besides that,the identification of metal inside SBA-15 was determined by comparing the pure SBA-15 with the incorporated metal on SBA-15. For this research,the characterization of the catalyst by selecting Zn as promoter have quiet similar characterization with noble metal that already investigate.